2011
DOI: 10.1007/s00277-011-1338-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of C282Y, H63D, and S65C mutations in hereditary HFE-hemochromatosis gene in Lithuanian population

Abstract: HFE-hemochromatosis is a common autosomal recessive disease caused by HFE gene mutations and characterized as iron overload and failure of different organs. The aim of this study was to determine the prevalence of C282Y (c.845 G>A), H63D (c.187 C>G), and S65C (c.193A>T) alleles of HFE gene in the Lithuanian population. One thousand and eleven healthy blood donors of Lithuanian nationality were examined in four different ethnic Lithuanian regions to determine HFE gene alleles and genotype frequencies. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Finally, it was recently reported that patients infected with HCV genotype 3a had higher expression of hepatic MHC class I and HFE (Cardoso et al 2004). Considering that the C282Y mutation is reported more rarely than the H63D mutation (Candore et al 2002;Kucinskas et al 2012), it is not surprising that the number of C282Y-carrying patients was small in the studies in our meta-analysis. Meanwhile, in three of the enrolled studies, patients with the C282Y mutation displayed no SVR; however, the group of C282Y patients was too small to allow for detection of a statistically significant difference from the WT group (i.e.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Finally, it was recently reported that patients infected with HCV genotype 3a had higher expression of hepatic MHC class I and HFE (Cardoso et al 2004). Considering that the C282Y mutation is reported more rarely than the H63D mutation (Candore et al 2002;Kucinskas et al 2012), it is not surprising that the number of C282Y-carrying patients was small in the studies in our meta-analysis. Meanwhile, in three of the enrolled studies, patients with the C282Y mutation displayed no SVR; however, the group of C282Y patients was too small to allow for detection of a statistically significant difference from the WT group (i.e.…”
Section: Discussionmentioning
confidence: 75%
“…Subsequent stratification analysis revealed that the highest frequencies of C282Y occurred in the Irish (10.0%) and of H63D in the Basque (30.4%) . In contrast, the frequency of S65C mutation was lower than that of C282Y or H63D in all regions examined (Candore et al 2002;Kucinskas et al 2012).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Hereditary hemochromatosis is characterized by excessive iron overload and is most commonly caused by HFE gene mutations [2] . The frequency of the most common HFE mutation, C282Y, is 0.035 in Latvia and 0.026 Lithuania; however, the frequency of hereditary hemochromatosis is lower at 0.013 [5] . Alpha-1 antitrypsin deficiency is caused by the absence of the proteinase inhibitor alpha-1 antitrypsin, and affected patients develop liver disease and emphysema in the third or fourth decade of life [3] .…”
Section: Introductionmentioning
confidence: 98%
“…The patients in liver fibrosis group underwent percutaneous liver biopsy and were included in the study if stage 1 to 3 fibrosis was documented by histological evaluation using METAVIR score [15]. Control samples came from our previous genotyping study on the prevalence of HFE mutations in the Lithuanian population and included 498 voluntary, unrelated Lithuanian blood donors [16]. The study protocol conforms to the ethical guidelines of the 1975 Declaration of Helsinki (6th revision, 2008).…”
Section: Patientsmentioning
confidence: 99%